Effect of Mannitol Hydration as Renoprotective on Cisplatin Induced Nephrotoxicity (CIN) in Head and Neck Cancer Patients - Mareta Rindang, Andarsari; Yunita Dyah, Kusumaningrum; Rosy Nurlita, Hapsari; Dwi Hari, Susilo; Dewi Wara, Shinta (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Cisplatin is a cytostatic agent used as treatments in head and neck cancer patients.Nephrotoxicity is one of cisplatin major side effects. This study aimed to evaluate the renoprotectiveeffect of mannitol-hydration administration in head and neck cancer patients who receive cisplatinchemotherapy. Methods: This was a cohort observational study to analyze the renal function of head andneck cancer patients who receives cisplatin before and after mannitol-hydration administration in IRNASurgery and Soekardja Room of Chemotherapy at RSUD Dr. Soetomo Surabaya during June – September2018. The data obtained were BUN, SCr, and eClCr Cockroft-Gault of each cycle. Result: A total of 52patients were evaluated. The average value of creatinine serum, creatinine clearance, and BUN at each cyclewere fluctuate. However, the average value of creatinine serum and BUN were within the normal limit.The result of statistical analysis using paired t-test in those parameters at each cycle were not statisticallysignificant (p > 0,05) after mannitol administration except during first cycle to second cycle the SCr increasedsignificantly and eClCr was decreased significantly (p-value 0,024; 0,006, CI 95% respectively ). At fourthcycle the eClCr also decreased significantly (p value 0,008, CI 95%). Conclusion: The renoprotective effectof mannitol in head and neck cancer patients who receive cisplatin chemotherapy is sufficiently adequatewhich can maintain the value of BUN and creatinine serum of patients at each cycle within the normal limit.